AP/VP specific equivalent viscous damping model for base-isolated buildings characterized by SDOF systems. (15th March 2016) - Liu, Tao; Zhang, Qilin
Highlights: Effect of peak ground acceleration to peak ground velocity ratio AP / VP is studied. An AP / VP specific equivalent viscous damping model is proposed. Estimation accuracy of the proposed model is greatly improved. Abstract: In this paper, an AP / VP specific equivalent viscous damping model is proposed through regression analysis to predict the maximum inelastic displacement of base-isolated buildings characterized by SDOF system. In order to present comprehensive results, a large number of parameters are specified for bilinear SDOF systems, i.e., 8 initial natural periods between 0.1 s and 1.5 s, 16 ductility ratios ranging from 2 to 50 and 4 post-to-pre-yield stiffness ratios: 0.0, 0.05, 0.1 and 0.2. A total of 45 earthquake ground motions are selected as seismic input and classified into three groups according to different frequency contents represented by peak ground acceleration to peak ground velocity ratios ( AP / VP ). Results show that the AP / VP ratio is of significant importance for the estimation accuracy of equivalent linearization method, especially for buildings with relatively small post-to-pre-yield stiffness ratio. Finally, the estimation accuracy of the proposed model is verified through comparison with other models.